Intraoperative electron radiotherapy for the management of aggressive fibromatosis - Röder, Falk; Timke, Carmen; Oertel, Susanne; Hensley, Frank W.; Bischof, Marc; Münter, Marc; Weitz, Jürgen; Büchler, Markus W.; Lehner, Burkhard; Debus, Jürgen; Krempien, Robert (International journal of radiation oncology, biology, physics, 2010)
Purpose - We analyzed our experience with intraoperative electron radiotherapy (IOERT) followed by moderate doses of external beam radiotherapy (EBRT) after organ-sparing surgery in patients with primary or recurrent aggressive fibromatosis. - Methods and Materials - Indication for IOERT and postoperative EBRT as an individual treatment approach to avoid mutilating surgical procedures was seen when complete surgical removal seemed to be unlikely or impossible. A total of 31 lesions in 30 patients were treated by surgery and IOERT with a median dose of 12 Gy. Median age was 31 years (range, 13-59 years). Resection status was close margin in six lesions, microscopically positive in 13, and macroscopically positive in 12. Median tumor size was 9 cm. In all, 25 patients received additional EBRT, with a median dose of 45 Gy (range, 36-54 Gy). - Results - After a median follow-up of 32 months (range, 3-139 months), no disease-related deaths occurred. A total of five local recurrences were seen, resulting in actuarial 3-year local control rates of 82% overall and 91% inside the IOERT areas. Trends to improved local control were seen for older age (>31 years) and negative margins, but none of these factors reached significance. Perioperative complications were found in six patients, in particular as wound healing disturbances in five patients and venous thrombosis in one patient. Late toxicity was seen in five patients. - Conclusion - Introduction of IOERT into a multimodal treatment approach in patients with aggressive fibromatosis is feasible with low toxicity and yielded good local control rates even in patients with microscopical or gross residual disease.
Erstmals am 3. August 2009 online veröffentlicht
Gesehen am 14.06.2023
Presented in part at the 49th Annual Meeting of the American Society for Therapeutic Radiology and Oncology (ASTRO), Oct 28–Nov 1, 2007, Los Angeles, CA